PRIORITIZATION OF OVERALL SUSTAINABILITY FACTORS OF CLOUD MANUFACTURING THROUGH AHP AND FUZZY AHP APPROACH - Mohneesh Kumar SHARMA (Scientific Journal of Silesian University of Technology. Series Transport)
In this global competitive environment, with the recent advancement in information and communication technologies, the industries are adopting new strategies to sustain. Cloud manufacturing is a new technology that utilizes data analytics for better decision-making resulting in more productive, cost, and energy-efficient operations. Increasing awareness towards a clean environment and optimum utilization of resources in manufacturing motivate us to study cloud manufacturing in the context of sustainability. Therefore, a significant number of social, environmental, and economic factors of cloud manufacturing are identified through literature review, and experts’ opinions and prioritization of these factors are obtained through the AHP and Fuzzy AHP methods. As per the final results obtained, “Efficient use of resources” is the most significant factor for the adoption of cloud manufacturing process and “Remote material monitoring” is the least significant factor amongst all the factors taken under consideration. The results are found to be consistent and accurate as per the value of consistency ratio. And the percentage obtained for social, environmental, and economic factors proves the cloud manufacturing process to be a sustainable manufacturing process.